Hyaluronic acid for advanced therapies: Promises and challenges. (August 2019) - Gallo, Nunzia; Nasser, Heba; Salvatore, Luca; Natali, Maria Lucia; Campa, Lorena; Mahmoud, Mohamed; Capobianco, Loredana; Sannino, Alessandro; Madaghiele, Marta
Graphical abstract: Highlights: Global hyaluronic acid (HA) market expected to reach USD 15.4 billion by 2025. HA involved in many biological pathways in physiological and pathological states. Chemical modifications to prolong HA half-life in vivo may challenge the safety. Cancer therapy and tissue regeneration as advanced HA applications. Need to improve HA production to face increasing demand at sustainable costs. Abstract: Hyaluronic acid (HA), also termed hyaluronan, is a key extracellular matrix glycosaminoglycan that not only provides tissue hydration, but also shows intrinsic bioactivity towards cellular proliferation, differentiation and inflammatory response. These properties make HA attractive both as a potential target for the treatment of several diseases and as an effective biomaterial to control cell behavior. This concise review aims at emphasizing the increasing role of HA as a promising biomaterial for advanced medical applications that include, among others, the development of targeted therapies for cancer treatment and the development of scaffolds for regenerative medicine. Although the bioactive mechanisms of HA are not fully understood, its molecular weight and purity are well known to affect the cellular and immunological responses to HA-based products. Furthermore, in spite of the complex translation of novel HA-based medical devices from the lab bench to the clinic, a rapid growth of the HA market is foreseen in the next future, also due to the growing aging of the population and the increasing demand for anti-aging products. In this perspective, the industrial HA production is briefly addressed, with reference to the technological issues that are currently undergoing extensive research to improve the HA yield and quality, in an attempt to meet the quickly rising HA demand.